Pengaruh Latar Belakang Pendidikan, Pengalaman Audit Dan Gender Terhadap Kualitas Audit: (Studi Empiris pada Kantor Akuntan Publik di Wilayah Bekasi & DKI Jakarta) - Cindy Anggita N; Istianigsih Istianigsih; Maidani Maidani; Idel Eprianto (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
This research aims to examine the "Influence of Educational Background, Audit Experience, and Gender on audit quality (Empirical Study at Public Accountant Offices in the Bekasi and DKI Jakarta Regions)." The population in this study consists of auditors working in Public Accountant Offices in the Bekasi and DKI Jakarta regions. Variables identified in this research include Audit Quality as the dependent variable, while Educational Background, Audit Experience, and Gender play roles as independent variables. The sampling method applied is non-purposive sampling or accidental sampling, and a total of 79 respondents were successfully obtained. Data analysis was conducted through Descriptive Statistical Analysis, Outer Model Test, Inner Model Test, and Hypothesis Test. The research results indicate that Educational Background and Audit Experience have a significant impact on Audit Quality, while Gender is not proven to influence Audit Quality.